1997
DOI: 10.1046/j.1469-7580.1997.19020209.x
|View full text |Cite
|
Sign up to set email alerts
|

Projections of chemically identified myenteric neurons of the small and large intestine of the mouse

Abstract: The projections of different subpopulations of myenteric neurons in the mouse small and large intestine were examined by combining immunohistological techniques with myotomy and myectomy operations. The myotomies were used to examine the polarity of neurons projecting within the myenteric plexus and showed that neurons containing immunoreactivity for nitric oxide synthase (NOS), vasoactive intestinal peptide (VIP), calbindin and 5-HT projected anally, while neurons with substance P (SP)-immunoreactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
1
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 53 publications
3
92
1
2
Order By: Relevance
“…Quantitative analysis at P30 demonstrated Cre-dependent EYFP expression in 100% of SOX10 + enteric glia, 62% of distal small bowel myenteric neurons, 17% of colon myenteric neurons, 93% of distal small bowel nNOS-expressing myenteric neurons, 90% of distal small bowel calretinin + myenteric neurons, 76% of colon nNOS + myenteric neurons, and 80% of colon calretinin + myenteric neurons (Supplemental Figure 5). We also noted that, in our mice, 12% of colon myenteric neurons had nNOS immunoreactivity and 12% had calretinin immunoreactivity, lower percentages than previously reported in BALB/c mice (25). Finally, we performed immunohistochemistry for PHOX2B in these mice at E10.5 and E11.5 (Supplemental Figure 6) and found that Cre-induced recombination occurred with some, but not all, ENS precursors by E10.5 and in almost all ENS precursors by E11.5.…”
Section: Rb1 Loss In the Ens Causes A Severe Intestinal Motility Disocontrasting
confidence: 44%
“…Quantitative analysis at P30 demonstrated Cre-dependent EYFP expression in 100% of SOX10 + enteric glia, 62% of distal small bowel myenteric neurons, 17% of colon myenteric neurons, 93% of distal small bowel nNOS-expressing myenteric neurons, 90% of distal small bowel calretinin + myenteric neurons, 76% of colon nNOS + myenteric neurons, and 80% of colon calretinin + myenteric neurons (Supplemental Figure 5). We also noted that, in our mice, 12% of colon myenteric neurons had nNOS immunoreactivity and 12% had calretinin immunoreactivity, lower percentages than previously reported in BALB/c mice (25). Finally, we performed immunohistochemistry for PHOX2B in these mice at E10.5 and E11.5 (Supplemental Figure 6) and found that Cre-induced recombination occurred with some, but not all, ENS precursors by E10.5 and in almost all ENS precursors by E11.5.…”
Section: Rb1 Loss In the Ens Causes A Severe Intestinal Motility Disocontrasting
confidence: 44%
“…Neural activity also influences differentiation, as (106). Studies using myotomy and myectomy followed by immunohistochemistry demonstrate that excitatory motor neuron axons project rostrally, while inhibitory motor neurons project caudally within the longitudinal axis of the myenteric plexus before entering circular or longitudinal muscle (106,107). Elegant models of enteric neuron circuitry now exist based on decades of work (1,22,(108)(109)(110), but mechanisms needed to establish these connections remain obscure.…”
Section: Ens Morphogenesis Does Not End When Encdcs Reach "The End"mentioning
confidence: 99%
“…Descriptions found on the literature assess several aspects of this subdivision of the autonomic nervous system [1][2][3][4][5] and reveal the richness of structure and organization of this neuronal population of magnitude similar to that of the spinal 6 . Systematization of the studies on the enteric neurons, especially those of the myenteric plexus of species such as the rat, mouse and guinea-pig, have permitted to determine, with relative precision, the functions of specific groups of neurons [7][8][9] . Due to the accessibility of the ENS, investigations about the alterations caused by pathophysiological states, such as diabetes, have been equally productive; there are reports on the literature [10][11][12][13] about the differential effects of diabetes on specific neurotransmitter systems and on neurons of diverse intestinal segments.…”
Section: Palavras-chave: Duodeno Neurônios Mientéricos Diabetes Agumentioning
confidence: 99%